MANAJEMEN PEMBELAJARAN DALAM UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA PESANTREN MODERN DARUL ‘ULUM KOTA BANDA ACEH (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2019)
Learning management in Islamic schools or Islamic boarding schools is a necessity in improving learning outcomes and management of the schools itself as part of the national education. The purpose of this study was to determine: the planning, implementation, and evaluation of learning at Darul ‘Ulum Islamic Boarding School of Banda Aceh. The research used descriptive method with qualitative approach. Data collection techniques used were: observation, interview, anddocumentation study. Subjects of the research were the Principal and Teachers. The results showed that the learning plan was prepared by the principal together with teachers, which included the setting of time allocation and effective weeks, the preparation of annual and semester programs, and the compilation of learning syllabus and lesson plan. Learning Implementation has been applied in accordance with management functions, that is the division of work in accordance with their respective capacities. Principal and teachers have carried out their roles and responsibilities. Evaluation and assessment aspects of school showed that the assessment process was adjusted and based on the lesson plan that had been developed. It can be concluded that the Principal and theteachers have been carrying out their role according to their respective duties. Sufficient facilities and infrastructure were available to support the success of the learning process. Nevertheless, there were some obstacles faced by the school such as, lack of time allocation and lack of students’ discipline. This problems can be used as evaluation materials in order to improve the learning management in the future for the sake of improving student learning outcomes.